UPAYA MENINGKATKAN PEMAHAMAN SISWA TENTANG KONSEP PERKALIAN BILANGAN CACAH DENGAN MENGGUNAKAN PENDEKATAN REALISTIK DI KELAS II SEKOLAH DASAR - Novi Rahmawati; Ratri Nuryani Qudwathullatifah; Ima Rismayanti (PERISKOP : Jurnal Sains dan Ilmu Pendidikan, 2020)
This research is motivated by the low understanding of students in learning mathematics about the concept of multiplication. This makes students' understanding of multiplication of whole numbers still low. Based on these problems, efforts are made to improve understanding of the concept of multiplication of whole numbers by using a realistic approach. This study begins with giving pretest to students, aiming to get an idea of understanding the concept of multiplication of whole numbers. This research method uses Classroom Action Research which consists of four stages, namely; planning, implementation, observation, and reflection. This research was carried out in two cycles, where from each cycle there was a significant increase so that a realistic approach could be applied to the material of multiplication of whole numbers..